Pengaruh Stres Kerja Dan Lingkungan KerjaTerhadap Semangat Kerja Karyawan Bri Cabang Bekasi - Ratnasari, Dewi, Dr. Triyono, S.E., M.Si (2016)
The purpose of this study was to know the effect of work stress variables on employee enthusiasm, environment variables on employee enthusiasm, and the effect of work stress variables and working environment together against employee enthusiasm. This research is quantitative methods used in this study. The primary data of questionnaires distributed directly to employees of Bank Rakyat Indonesia Branch Bekasi. Samples were taken in total sampling in order to obtain a sample of 60 respondents. Prior to the data analysis first tested the classical assumption of normality test and multicollinearity. The data analysis technique uses multiple linear regression analysis. Based on the results obtained by t test known value of variable stress work - with significance value 0,001, which means that there is a negative correlation very significant between stress work with enthusiasm. The results of the t test for an unknown price variable with significant value 0,000 then Ho is rejected and the significance level of 0.05 so that the working environment significantly on morale. Result of test F obtained by value significant 0,000, this matter indicate that the environmental variable and stres work by simultan have an effect on motivation work. R2 test figures obtained determination coefficient 0.398. This means that the stress of work and the work environment can affect the enthusiasm effectively and efficiently by 39.8%, while the remaining 60.2% is influenced by other variables that are not used in this study. Keywords: work stress, work environment, enthusiasm employee